Hagiographic and Hymnic Representations of Women, Dress, and Identity in the Early Christian East - Jenny Bledsoe (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
In the early Christian East, as now, dress indicated conformity or nonconformity to social norms, projecting and sometimes concealing the individual’s gender and religious identities in a social context and indicating their position in the Church hierarchy. In the vitae of female saints Pelagia of Antioch, Anastasia, and Mary of Egypt and the hymns of Ephrem the Syrian, dress also functioned as a textual device to illustrate fundamental changes in the life of the individual Christian and, especially in the case of Ephrem, to convey theological truths about virginity and the relationship between Christ and humanity to an audience of believers. Texts such as the hagiographies and hymns explored in this article were not merely enjoyable for readers or listeners. Rather, such texts were used in liturgy or at least closely associated with ecclesiastical life, and thus they were instructive of the proper ways in which the authors thought ordinary Christians ought to live.
Keywords: Hagiographic; Hymnic; Women; Dress; Christian; Religion